On the relationship between fertility, development and gender equality: A comparison of Western and MENA countries - Zafer Buyukkececi; Henriette Engelhardt-Wölfler (Comparative Population Studies (CPoS), 2021)
The changing macro-level relationship between fertility and development (i.e., the standard of living, health and education) from negative to positive for the most advanced economies has received considerable attention recently. Using aggregate data, we compare the relationship between fertility and development in Western countries with the Middle East and North Africa (MENA) region, where fertility rates are higher than in other regions with identical levels of development. To understand the drivers of this association, we further link fertility to the components of development as well as female labour force participation separately. Our findings show that fertility and development were positively associated for only a short period in Western countries and that the relationship turned negative again in recent years. Recent data also show that there is no significant relationship between fertility and development in MENA countries. These findings indicate that the well-acknowledged theories of fertility and development do not apply in every context.
urn:nbn:de:bib-cpos-2021-09en9
Keywords: 300; Fertility; Human Development Index; MENA region